Expansion Clauses Application in Pan Balang Tamak Text - Suardana, I Ketut; Sedeng, I Nyoman; Sutama, Putu (e-Journal of Linguistics; Vol 14 No 1 (2020): e-jl January, 2020)
Pan Balang Tamak text is one of famous Balinese texts in Balinese community. But, unfortunately, the popularity of the text has declined since more than years ago especially in the youth. This is because of more interesting and modern entertainment. This phenomenon made the stakeholders feel worried because it led it to get extinct therefore, the stake holders anticipated it. One of the efforts to prevent from the extinct was to write an Balang Tamak text. The text was written in some version with their own styles. However, the essence of all variances is similar. The text belongs to be narrative text therefore needs more abstract comprehension to find the character of the figures, message and ideology of the text. Most of the communities comprehended the text from literal point of view. This was the reason why the text was viewed to different interpretation about the characters of the text. Besides that, the clauses within the complexes employed were not comprehended well based on the functions in the clauses complexes. To find the characteristic of the figures of the text, expansion clause becomes prime concern. This paper analyzed the clause functions within the expansion clauses. The data were taken from Satua satua Bali Pan Balang Tamak (2014).  The theory used to analyze the data was the theory of clause complex proposed by Halliday. The method hired for this research was library research by syntactical technique. The finding of the research suggested that all kinds of expansion clause be hired in the text such as: elaboration, extension and enhancement. Enhancement clauses were found in the most variety.